2021
DOI: 10.48550/arxiv.2107.09042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Jam Session to Recital: Synchronous Communication and Collaboration Around Data in Organizations

Abstract: Prior research on communicating with visualization has focused on public presentation and asynchronous individual consumption, such as in the domain of journalism. The visualization research community knows comparatively little about synchronous and multimodal communication around data within organizations, from team meetings to executive briefings. We conducted two qualitative interview studies with individuals who prepare and deliver presentations about data to audiences in organizations. In contrast to prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Then, they would manually migrate information from notebooks to presentation tools like PowerPoint. But this process needs to switch between tools frequently, which is tedious and prone to error [8]. DS workers often reuse their past presentation slides [38], which still need them to manually adapt the slides' contents to a new notebook.…”
Section: Computational Notebook As An Artifact Of Data Science Techni...mentioning
confidence: 99%
See 1 more Smart Citation
“…Then, they would manually migrate information from notebooks to presentation tools like PowerPoint. But this process needs to switch between tools frequently, which is tedious and prone to error [8]. DS workers often reuse their past presentation slides [38], which still need them to manually adapt the slides' contents to a new notebook.…”
Section: Computational Notebook As An Artifact Of Data Science Techni...mentioning
confidence: 99%
“…Some prior works reported that DS workers might spend hours or even days to prepare the presentation slide after they finish their core technical modeling works [38]. The work is tedious and time-consuming due to multiple reasons: a) data scientists have to meticulously locate and distill essential information from the complex, messy, and sometimes fragmented experimental codes [29,39]; b) they need to organize these information to construct a story narrative; and, c) they also need to consider the specific domain context and audience backgrounds, and often add additional information (e.g., visualizations, explanations, and examples) to customize their presentation so that it can better engage the target audience and gain their trust [8,29,42].…”
Section: Introductionmentioning
confidence: 99%